The equality multiplier: How wage setting and welfare spending make similar countries diverge - Erling Barth; Karl Ove Moene (Institute for the Study of Labor (IZA), 2012)
The complementarity between wage setting and welfare spending can explain how almost equally rich countries differ in economic and social equality among their citizens. More wage equality increases the welfare generosity via political competition in elections. A more generous welfare state fuels wage equality via an empowerment of weak groups in the labor market. Together the two effects generate a cumulative process that adds up to a social multiplier explaining how equality multiplies. Using data on 18 OECD countries over the period 1976-2002 (determined by the availability of the generosity index of welfare spending) we test the main predictions of the model and identify a sizeable magnitude of the equality multiplier. We obtain additional support by using spending data to extend the panel up to 2007, and by applying another data set for the US over the period 1945-2001.
urn:nbn:de:101:1-2012080812379
Keywords: H53; I31; J31; 330; welfare state; wage inequality; Soziale Gerechtigkeit; Soziale Ungleichheit; Öffentliche Sozialausgaben; Lohnstruktur; OECD-Staaten